The Impact of Negligence Claims on CRNAs: A Qualitative Study. - Chambers, Pamela; LaCour, Meagan; Muratovic, Elvisa (AANA Journal, 2025)
Adverse events may cause emotional distress among clinicians. Negligence claims compound this stress, leading to emotional effects such as litigation stress syndrome. Repercussions of being named in a claim extend beyond the individual, affecting interpersonal relationships. There is a notable gap in research regarding the lived experiences of certified registered nurse anesthetists named in negligence claims. Eleven participants were recruited via social media who completed a demographic survey and were interviewed for up to 60 minutes. Data were coded through in vivo coding using thematic analysis. Forty six percent reported experiencing a patient death, 18% encountered a major event, and 36% faced a minor event. Participants described a range of emotions including "stressful, angry, suicidal, confident, and fearful." All participants were instructed to not discuss the claim, leading to feelings of isolation and loneliness. Additionally, none of the participants were aware of the resources provided by the American Association of Nurse Anesthesiology, indicating a lack of awareness regarding available support for addressing litigation stress syndrome. Due to significant feelings of isolation, the emotional toll of a negligence claim can affect an individual's mental health, leading to anxiety, depression, or anger that can affect their relationships with others.